Redefining political-administrative relationships in South Africa - Cameron, Robert (2010)
This article is an overview of shifting political-administrative relationships in South Africa, with particular reference to growing politicization (partisan control of the bureaucracy). Studies of politicization of public services are important because political involvement in management has often led to negative effects on service delivery. The article sets out a theoretical framework for political-administrative relationships, examining the growing politicization of public services, the impact of New Public Management (NPM) and political-administrative relationships in developing countries. It the looks at political-administrative relationships in South Africa, including the apartheid history, the development of a new framework in the democratic South Africa and politicization in the staffing of the public service. It examines three functional areas - the decentralization of powers, contract appointments and performance management - and discusses the implications of this changing framework for service delivery. The methodology consisted of interviews with a number of senior government officials, including three current directors-general and a former Minister for the Public Service and Administration, an analysis of government legislation, Public Service Commission (PSC) data including surveys, unpublished data of the Department of Public Service and Administration (DPSA), policy papers of the African National Congress (ANC) and an Organisation for Economic Co-operation and Development (OECD) study of political involvement in bureaucracies. The article concludes that growing politicization of the public service has contributed to poor service delivery, and that the South African government needs to place greater emphasis on merit as the basis for appointments and promotions. - Reproduced.
Keywords: Civil service - South Africa; Civil service